Dynamic similitude technique for predicting the behaviour of structures subjected to impact loads. (May 2022) - Wang, Tao; Ni, Lei; Wu, Tian; Wang, Yuexin; Xi, Xulong; He, Huan
Highlights: A scaled method for structures considering material strain-rate sensitivity and geometrical distortion is proposed. A loss function is developed to correct the velocity scaling factors, which can reflect the dynamic process of impact and can be applied to any form of strain rate sensitive constitutive equation. The efficiency of the proposed similitude methodology is tested on the impacted T-beam. Abstract: To predict the dynamic behavior of large-scale structures subjected to impact loads by similitude theory is an important design tool for engineers. However, structures under impact loads usually do not follow the usual similarity laws due to material strain-rate effects and geometrical distortion. This paper proposed a dynamic similitude method to predicting the behavior of structures subjected to impact loads where material strain-rate sensitivity and geometrical distortion are both considered. In this work, we firstly deduced a loss function of the dynamic yield stress to obtain the scaling correction factor to remove the strain rate effects by correcting initial impact velocity. Then a distortion factor related to the geometrical distortion was introduced to obtain a new velocity correction factor, which made it possible to reduce the effects of material strain-rate sensitivity and geometrical distortion together. The efficiency of the scaling approach presented in this paper was illustrated by the numerical simulations and experiments of a T-beam model under impact loading and the results showed a small deviation between the predictions of the model and the prototype.